PELAKSANAAN ZAKAT PROFESI BAGI APARATUR SIPIL NEGARA BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2011 TENTANG PENGELOLAAN ZAKAT (Studi Kasus di Kantor BAZNAS Kabupaten Tulungagung) - Yuniati, Anik; Fahrazi, Mahfudz (Universitas Islam Kadiri, 2024)
This study examines the Implementation of Professional Zakat for State Civil Servants Based on Law Number 23 of 2011 concerning Management of Zakat at the BAZNAS Office of Tulungagung Regency. The aims of this study are 1) to analyze the implementation of professional zakat by Tulungagung Regency BAZNAS towards the State Civil Apparatus based on Law Number 23 of 2011 concerning the management of zakat, 2) To analyze the inhibiting factors in the management of professional zakat for the State Civil Apparatus at BAZNAS Tulungagung Regency.The research method used in this research is empirical juridical research with a qualitative descriptive analytical approach. Data collection techniques were carried out by interviews, observation and documentation. The analysis technique used in this study is the syllogism method and interpretation using deductive thinking patterns. The research results show 1) the implementation of professional zakat by BAZNAS of Tulungagung Regency towards the State Civil Apparatus based on Law Number 23 of 2011 concerning the management of zakat is carried out by deducting employee salaries which are carried out every month by the treasurer.The employee salary deduction is only applied by employees of the State Civil Apparatus who earn above 3 million rupiah and are deducted from their gross monthly salary. Salary deducted by 2.5%, professional zakat from salary deductions entirely paid to BAZNAS Tulungagung Regency distributes it to 8 ashnaf. 2) The inhibiting factors in the management of professional zakat for the State Civil Apparatus at BAZNAS Tulungagung Regency include 1) The need for increased support from the government in the form of policies, 2) Lack of awareness of zakat through institutions, public awareness for zakat currently continues to increase, this is occursdue to a lack of trust in zakat institutions. 3) The need for increased funds for socialization.